2011
DOI: 10.1111/j.1540-8175.2011.01422.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Body Mass Index on Right Ventricular Systolic Functions in Normal and Mildly Obese Healthy Patients: A Velocity Vector Imaging Study

Abstract: The results of our study show no changes in the RV functions in obese and overweight who were otherwise healthy subjects. We also revealed a significant correlation between BMI and left ventricular diameters and wall thickness but no relation with RV diameters or functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
2
15
1
2
Order By: Relevance
“…In contrast to the above mentioned results, we and others 17,25,26) have found no association of RV function and increasing BMI in obese and/or overweight persons. Additionally, right atrial and right ventricular end-systolic and diastolic dimensions, as well as RV diastolic function did not differ significantly across increasing BMI categories.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In contrast to the above mentioned results, we and others 17,25,26) have found no association of RV function and increasing BMI in obese and/or overweight persons. Additionally, right atrial and right ventricular end-systolic and diastolic dimensions, as well as RV diastolic function did not differ significantly across increasing BMI categories.…”
Section: Discussioncontrasting
confidence: 42%
“…Additionally, right atrial and right ventricular end-systolic and diastolic dimensions, as well as RV diastolic function did not differ significantly across increasing BMI categories. 17,25,26) On the other hand, these studies consistently found significant alterations of LV parameters, implying more sensible adaptions of the left than the right heart to increasing adiposity. The reasons for the incongruent study results remain speculative.…”
Section: Discussionmentioning
confidence: 86%
“…Childhood obesity is one of the most serious public health problems (1)(2)(3). Obesity and cardiac involvement has been reported frequently in the literature, but analysis of regional myocardial function in children by two-dimensional (2D) speckle tracking echocardiography (STE) is rarely documented (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Também se tem demonstrado que a infiltração gordurosa do miocárdio repercute não só na estrutura, mas também na mecânica ventricular [11][12][13][14] . Esse aumento no volume circulante foi corroborado no presente estudo com uma associação direta estatisticamente significativa entre o débito cardíaco, o volume de ejeção e o índice de massa corpórea, identificando-se um valor máximo quando o índice de massa chega a 35 e 37 kg/m No estudo do impacto do índice de massa corpórea sobre a disfunção diastólica do ventrículo esquerdo, Cil e cols.…”
Section: Discussionunclassified
“…As variáveis para a avaliação da função sistólica e diastólica do ventrículo direito não mostraram mudanças relevantes relacionadas com o índice de massa corpórea, resultados coerentes com a literatura, na qual se descreve que a função do ventrículo direito não se vê afetada pelo sobrepeso, nem a obesidade 12,18 . 8 demonstraram que a normalização da massa ventricular esquerda pela área de superfície corpórea e pelo comprimento introduz artefatos relacionados com a indexação da massa ventricular à massa corpórea e erros na estimativa do impacto do sobrepeso.…”
unclassified